Багануурын ордын нөөцийн шинэчилсэн тооцооны үр дүнгээс - Х.Баттөгс,; Б.Эрдэнэцогт, (Geological Issues, 2023)
Baganuur lignite mine is located on the northern margin of Choir-Nyalga basin of Eastern Mongolian coal- and oil shale-bearing province. The basin covers an area of approximately 50.000 sq km. The mine is situated in a 14 km long and 5 km wide graben-syncline structure, filled with Cretaceous and Cenozoic deposits. In total 23 coal seams, including three main seams at the bottom. Seam 2, Seam 2a and Seam 3, are hosted in Lower Cretaceous Khukhteeg Formation. The net thickness of each three main seams ranges from 10.3 m to 98 m. The first coal exploration program for Baganuur deposit was conducted during the period from 1974 to 1975. consisting of 469 drillholes, totaling 49,800 line meters. Based on this data, initial coal reserves were estimated to be 599.8 Mt. In 1988, coal reserves were updated to 708.2Mt based on additional drilling program, composed of 125 drillholes for a total of 18,601 line meters. Since the initiation of mining in 1975, a total of 99.4Mt coal reserves have been depleted and coal reserves as well as feasibility studies are need to be revised. Thus, in 2014, two phases of drilling program were completed. The program consists of a total of 82 core holes, totaling 14.393.3 line meters. Based on the newly acquired data as well as historical pre-2014 drillhole data, geological model of Baganuur coal seams was constructed by using MINEX software and coal reserves was estimated to be 809 Mt, which is 100 Mt higher than previous coal reserve estimation.